Proceedings of the 7th ACM/IEEE-CS Joint Conference on Digital Libraries 2007
DOI: 10.1145/1255175.1255215
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive graphical approach to entity resolution

Abstract: Entity resolution is a very common Information Quality (IQ) problem with many different applications. In digital libraries, it is related to problems of citation matching and author name disambiguation; in Natural Language Processing, it is related to coreference matching and object identity; in Web application, it is related to Web page disambiguation. The problem of Entity Resolution arises because objects/entities in real world datasets are often referred to by descriptions, which might not be unique identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 35 publications
(64 reference statements)
0
39
0
3
Order By: Relevance
“…Based on the real data sets, the paper [6] evaluates the efficiency of entity unity. In addition, there are other aspects of the research, like heuristic method [7], distance function [8], Markoff chain [9] and so on. At present, the latest entity recognition method using machine learning [10] algorithm, machine learning library has brought the realization of many classifiers.…”
Section: Related Workmentioning
confidence: 99%
“…Based on the real data sets, the paper [6] evaluates the efficiency of entity unity. In addition, there are other aspects of the research, like heuristic method [7], distance function [8], Markoff chain [9] and so on. At present, the latest entity recognition method using machine learning [10] algorithm, machine learning library has brought the realization of many classifiers.…”
Section: Related Workmentioning
confidence: 99%
“…Over the past few years we have developed a powerful disambiguation engine that we refer to as the Relationshipbased Data Cleaning (RelDC) [3]- [6], [8], [10]. In this section we outline the principal methodology employed by the RelDC framework.…”
Section: B Relationship-based Data Cleaningmentioning
confidence: 99%
“…Further details can be found in [5], [8]. Application of RelDC to the Grouping problem is described in [3], [4].…”
Section: B Relationship-based Data Cleaningmentioning
confidence: 99%
“…This assumption does not hold for scenarios where relevant data is distributed between different instances, which are related to each other. Thus, approaches, which analyze relations between data instances of different classes, have received significant attention in recent years (e.g., [3], [7], [8], [9]). One algorithm focusing on exploiting links between data objects for personal information management was proposed in [3], where the similarities between interlinked entities are propagated using dependency graphs.…”
Section: Related Workmentioning
confidence: 99%
“…One algorithm focusing on exploiting links between data objects for personal information management was proposed in [3], where the similarities between interlinked entities are propagated using dependency graphs. RelDC [7] proposes an approach based on analyzing entity-relationship graphs to choose the best pair of coreferent entities in case when several options are possible. The authors of these algorithms reported good performance on evaluation datasets and, in particular, significant increase in performance achieved by relation analysis.…”
Section: Related Workmentioning
confidence: 99%